Plenty more to come - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'Take advantage of Spore, after all, it is yours' was the message given to readers in an early issue, fourteen years ago. At the turn of the Millennium, we look back at the story so far to see how, and how many, readers are putting Spore to good...